SEEDING DOUBTS ABOUT VOTING BROADLY AND STRATEGICALLY: TRUMP AND BIDEN RHETORIC ONLINE IN THE 2020 U.S. PRESIDENTIAL ELECTION - Stromer-Galley, Jennifer; Kim, Pyeonghwa; Khoury, Christy; McKernan, Brian; Hemsley, Jeff (AoIR Selected Papers of Internet Research, 2023)
When rioters attacked the U.S. Capitol on January 6, 2021, they did so mistrusting the electoral process and believing that Donald Trump had been robbed of the presidency. Presidential rhetoric has the power to shape the attitudes of the public and steer the country (Mercieca, 2020). Indeed, presidential rhetoric has the power to shape what Taylor (2004) describes as the social imaginary – the rhetorical construction of a version of a shared reality that takes hold in public discourse and public consciousness. Trump’s rhetoric in 2020 around the vote continued a narrative that he had started when he took office. In this study, using the framework of social imaginaries, we qualitatively and inductively analyze messaging on campaign social media accounts around the 2020 presidential campaign. We also examine the Facebook advertisements and the targets of those ads specifically around the vote. We compare Trump’s rhetoric to that of his opponent Joe Biden to contrast the distinct imaginaries around the vote each political candidate articulated. We find that Trump relied on his social media accounts to sow distrust of the vote process and doubt about the accuracy of the vote count on Election Day. More concerning, we also find that Trump attacked the voting process through his paid advertising on Facebook, targeting voters in key battleground states.